New Urban Development : Looking Back to See Forward - Gruen, Claude (Book collections on Project MUSE., 2012)
New Urban Development traces how locally induced housing cost increases led federal policy-makers to toss out the safeguards against lending excesses that had been put in place during the 1930s. But the story begins much earlier, during the colonial era, continuing up through the mortgage collapse that ushered in the recession of 2008. In his sweeping history of these issues, Gruen considers gentrification, environmentalism, sprawl, anti-sprawl movements, and more. His clarification of how urban development change occurs backs up his recommendations for increasing the production of housing and replacing obsolete commercial and industrial spaces with development that serves the twenty-first-century economy. New Urban Development specifies thirteen changes to policies at the federal, state, and local levels to provide better and less expensive urban housing, desirable neighborhoods, and thriving workplaces across the country.